Military Culture and Its Impact on Mental Health and Stigma - A. Ganz; Chikako Yamaguchi; Bina Parekh; Gilly Koritzky; Stephen E. Berger (The University of Alabama, 2022)
This article reports two studies that used the Ganz Scale of Identification with Military Culture (GIMC), developed for these studies, to evaluate the relationships between military culture and aspects of mental illness, such as stigma (Study 1), substance use, and trauma (Study 2). The first two authors are veterans of the United States Armed Forces. Study 1 found that active-duty military scored higher on the GIMC total score, and on the component values of duty, selfless service, honor, and personal courage than did a general population sample, but not on the values of loyalty, integrity, and commitment. Level of GIMC endorsement (low, moderate, high), was related to attitudes toward those suffering from mental illness. Additionally, level of GIMC endorsement was found to be either a risk or protective factor toward self-harm and suicide. Study 2 found that service personnel who had sought mental health treatment after joining the military reported less concerns about whether such treatment would hurt their careers than did those who did not seek mental health services. Combined, the results of the two studies indicate that acculturation to the military culture can have positive or negative effects, and mental health stigma and concern about one's future in the military are impediments to service members obtaining mental health services.